Caribbean icons in science, technology & innovation. Vol. 2 (The Institute Port-of-SpainTT, 2009)
Presents information on the lives of Caribbean citizens who have attained a high level of distinction in their fields of science and technology.
Keywords: BIOGRAPHIES